Рыцари Звездного замка: повесть / С. С. Сухинов - Сухинов Сергей Стефанович (Чародеи, 2000)
Экземпляры: ф.13 (20180122) / Инвентарный номер: 31627 / Цена: 22.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 91 / ББК: 84(2Рос=Рус)6